Engineering mechanics. statics - Meriam, J. L.; Kraige, L. G.; Bolton, J. N. (John Wiley & Sons, 2016)
Engineering Mechanics: Statics has provided a solid foundation of mechanics principles for more than 60 years. Now in its eighth edition, the text continues to help students develop their problem-solving skills with an extensive variety of engaging problems related to engineering design. To help students build necessary visualization and problem-solving skills, the text strongly emphasizes drawing free-body diagrams, one of the most important skills needed to solve mechanics problems.